Carbon dioxide adsorbent as well as preparation method and application thereof

The solid phase mixing method is used to mix marine biological waste with magnesium oxide to prepare efficient carbon dioxide adsorbents, which solves the disadvantages of liquid adsorbents and traditional magnesium-based adsorbents, and achieves low-cost and environmentally friendly carbon dioxide capture effect, which is suitable for large-scale Scale application.

CN119236871APending Publication Date: 2025-01-03DALIAN MARITIME UNIVERSITY

Patent Information

Application Number
CN202411646600.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

In the existing carbon dioxide capture technology, liquid adsorbents have problems such as strong corrosiveness, high cost, large regeneration energy consumption and toxic by-products. Traditional magnesium-based adsorbents have high reaction temperature, large regeneration energy consumption and limited adsorption capacity. Preparation methods are as follows: Wet chemistry, sol-gel method and vapor deposition method have problems such as environmental pollution and high costs.

Method used

The solid phase mixing method is used to mix marine biological waste with magnesium oxide, and carbon dioxide adsorbent with high CO2 adsorption capacity and cycle stability is prepared by calcining and grinding, avoiding the disadvantages of liquid adsorbents and simplifying the preparation process.

Benefits of technology

It realizes low-cost and environmentally friendly carbon dioxide adsorbent preparation, improves the CO2 adsorption capacity and cycle stability of MgO, reduces the preparation cost, is suitable for large-scale production, and avoids the environmental and safety risks of liquid adsorbents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119236871A_ABST
    Figure CN119236871A_ABST
Patent Text Reader

Abstract

The invention discloses a carbon dioxide adsorbent and a preparation method and application thereof.The preparation method comprises the following steps that a biological shell material is cleaned and then dried, the pretreated biological shell material is ground, and coarse shell powder is obtained; sequentially calcining and grinding the coarse shell powder in a protective atmosphere to obtain shell micro powder; mixing the shell micro powder with a magnesium oxide solid phase, calcining in a protective atmosphere, and grinding to obtain the carbon dioxide adsorbent. According to the invention, a solid-phase mixing method is adopted, and the marine biological waste with specific content and magnesium oxide are mixed, so that the mutual cooperation and mutual synergism among the raw material components can be fully exerted, the element composition and microstructure of the adsorbent material can be effectively regulated and controlled, and by virtue of the preparation method which is easy to operate and low in cost, the adsorbent material can be prepared. The obtained novel carbon dioxide adsorbent can improve the CO2 adsorption capacity and cycle stability of MgO, and can stably maintain high carbon dioxide adsorption rate and adsorption capacity for a long time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of carbon capture technology, and more specifically, to a carbon dioxide adsorbent and a preparation method and application thereof. Background Art

[0002] The energy system of today's social development mainly relies on chemical energy such as coal, oil, and natural gas. During the energy conversion process, a large amount of carbon dioxide will be released, leading to global warming, thus triggering the greenhouse effect and causing natural disasters. According to current reports and commercial applications, carbon capture, utilization and storage (CCUS) technology is a very promising carbon neutral method, especially for high-emission industries such as coal-fired power plants and non-ferrous metal factories.

[0003] Among the CO2 capture methods, metal oxides have attracted much attention due to their simplicity, high efficiency and economic feasibility. In recent years, magnesium oxide (MgO) has become a highly regarded metal oxide for CCUS applications based on its simple and stable cubic structure and the formation of amorphous carbonates when combined with CO2. In addition, MgO has an ideal theoretical adsorption capacity and environmental compatibility, and has great application potential in process industries.

[0004] At present, liquid adsorbents are the most widely used in the field of carbon dioxide capture, especially in large-scale industrial carbon capture. At present, liquid carbon dioxide adsorbents include amine solutions (such as monoethanolamine, MEA), ionic liquids and functionalized solvents. These materials usually have high adsorption capacity and fast adsorption rate. Ionic liquids have gradually become a research hotspot due to their low volatility and high thermal stability. Functionalized solvents, such as amine solvents, improve the capture capacity of carbon dioxide by introducing specific functional groups into the solvent molecular structure. However, liquid adsorbents all have more or less problems. For example, amine solutions are highly corrosive, easily causing damage to equipment, and require frequent maintenance and replacement; they will also degrade during the adsorption and desorption process, which will greatly affect the adsorption efficiency and increase operating costs; in addition, there are problems such as excessive regeneration energy consumption, the production of toxic byproducts and high preparation costs.

[0005] Therefore, solid carbon dioxide adsorbents have become an important research direction in the field of carbon capture due to their high adsorption capacity, stability, low energy consumption regeneration and environmentally friendly characteristics. For CO2 capture, the carbonation / calcination reaction of magnesium oxide-based adsorbents can be used to cyclically capture CO2. The reaction formula is as follows:

[0006] MgO+CO2→MgCO3

[0007] MgCO3→MgO+CO2

[0008] Magnesium-based adsorbents capture CO2 primarily through chemical adsorption, a process that involves a chemical reaction between CO2 and active sites on the adsorbent surface. Traditional magnesium-based adsorbents have some limitations, such as high reaction temperature, high regeneration energy consumption, and limited adsorption capacity.

[0009] Therefore, many researchers are committed to developing new magnesium-based adsorbents to improve their CO2 adsorption efficiency at ambient temperature and reduce costs. In recent years, some progress has been made by modifying magnesium-based materials, including doping with other metal ions, using porous support materials and surface modification. For example, by combining magnesium-based materials with porous support materials with high porosity (such as activated carbon, zeolite or porous silicon), the specific surface area and pore volume of the adsorbent can be increased, thereby increasing its CO2 adsorption capacity. Although the magnesium-based adsorbents improved by these methods perform well on a laboratory scale, they still face some challenges in industrial applications, especially in terms of the cost, ease of handling and environmental friendliness of the adsorbent raw materials.

[0010] At present, the preparation methods for magnesium oxide-based adsorbents are mainly divided into wet chemical method, sol-gel method and vapor deposition method. The wet chemical method synthesizes magnesium oxide-based adsorbents through chemical reactions in solution. The characteristics of the product can be controlled by adjusting reaction conditions such as temperature, pressure, pH value and reaction time. This method may involve the use of toxic chemicals, and the waste generated during the preparation process needs to be properly handled, which will cause a large burden on the environment. Sol-gel method (Sol-gel) is to form a gel through the hydrolysis and polymerization reaction of the precursor, and obtain a magnesium-based adsorbent after drying and heat treatment. A uniform and porous magnesium-based adsorbent can be prepared, but high-cost and harmful chemicals may be used in the process, and the preparation cycle is long and energy consumption is high. The vapor deposition method refers to introducing a magnesium-containing gas precursor into a reaction chamber at high temperature and depositing it on a substrate to obtain a magnesium-based adsorbent, but the vapor deposition method needs to be carried out under high temperature and low pressure, which makes the equipment complex and costly, and the vapor deposition method is slow, which will affect production efficiency to a certain extent. Summary of the invention

[0011] The purpose of the present invention is to overcome the above-mentioned defects of the prior art and provide a carbon dioxide adsorbent and a preparation method and application thereof. By adopting a solid-phase mixing method and mixing a specific amount of marine biological waste and magnesium oxide, the mutual coordination and synergy between the raw material components can be fully exerted, and the elemental composition and microstructure of the adsorbent material can be effectively regulated. With an easy-to-operate and low-cost preparation method, the obtained new carbon dioxide adsorbent can improve the CO2 adsorption capacity and cycle stability of MgO, and can stably maintain a high carbon dioxide adsorption rate and adsorption capacity for a long time.

[0012] To achieve the above object, the technical solution of the present invention is as follows:

[0013] A method for preparing a carbon dioxide adsorbent comprises the following steps:

[0014] (1) washing the bioshell material and then drying it to obtain a pretreated bioshell material;

[0015] (2) grinding the pretreated biological shell material to obtain shell coarse powder;

[0016] (3) calcining the coarse shell powder under a protective atmosphere, and grinding the calcined product after cooling to room temperature to obtain shell fine powder;

[0017] (4) The shell micropowder and magnesium oxide solid phase are mixed, the mixed product is calcined under a protective atmosphere, and then ground to obtain the carbon dioxide adsorbent.

[0018] Optionally, in step (1), the drying temperature is 100° C. to 150° C.; and the drying time is 12 h to 24 h.

[0019] Optionally, in step (2), the grinding specifically includes the following steps: crushing the pretreated bioshell material and grinding it for 1 hour to 2 hours, then selecting a 600-mesh to 1200-mesh sieve to sift out the powder, collecting the residual bioshell fragments in the sieve and grinding it again for 0.5 hour to 1 hour, collecting the powder, and repeating the operation 3 to 6 times.

[0020] Optionally, in step (3), the calcination includes: calcining at 200°C to 400°C for 1h to 2h, then heating to 500°C to 600°C at a heating rate of 10°C / min to 20°C / min and calcining for 1h to 2h.

[0021] Optionally, the particle size of the shell micropowder is 40 microns to 125 microns.

[0022] Optionally, in step (4), the mass ratio of the shell micropowder to the magnesium oxide is 1:(1-9).

[0023] Optionally, in step (4), the calcination includes: calcining at 200°C to 400°C for 1h to 2h, then heating to 500°C to 600°C at a heating rate of 10°C / min to 20°C / min and calcining for 1h to 2h.

[0024] Optionally, the particle size of the carbon dioxide adsorbent is 40 microns to 125 microns.

[0025] The invention also discloses a carbon dioxide adsorbent prepared by the above preparation method.

[0026] The invention also discloses an application of the carbon dioxide adsorbent prepared by the above-mentioned preparation method in capturing carbon dioxide.

[0027] Optionally, the carbon dioxide adsorbent is used for adsorbing carbon dioxide in air and flue gas.

[0028] Optionally, the temperature at which the carbon dioxide adsorbent adsorbs carbon dioxide is 300°C to 500°C.

[0029] Implementing the embodiments of the present invention will have the following beneficial effects:

[0030] (1) The synthesis method of the novel magnesium-based adsorbent proposed in the present invention is low-cost and simple and convenient to operate. First, the adsorbent synthesis process does not require the use of solvents, and the reaction process is more environmentally friendly. At the same time, naturally occurring substances in nature are selected as adsorbent dopants after simple treatment, which greatly reduces the cost of adsorbent preparation.

[0031] (2) The solid phase reaction method used in the synthesis method proposed by the present invention has the advantages of high selectivity and high yield. This is because the reaction occurs between solids, and the quality and quantity of the product can be optimized by precisely controlling the reaction conditions. In addition, the solid phase reaction method used in the synthesis method can prepare materials with uniform particle size and controllable strength, which is crucial for many industrial applications.

[0032] (3) The synthesis method proposed in the present invention can also avoid or reduce the hard agglomeration phenomenon that is easy to occur in the liquid phase. In general liquid phase reactions, the reactants tend to form hard agglomerates, but in this synthesis method, this phenomenon can be effectively avoided or reduced, so that the synthesis efficiency of the adsorbent is significantly improved.

[0033] (4) Compared with MgO, the adsorbent prepared by the simple, easy-to-operate and low-cost magnesium-based adsorbent synthesis method proposed in the present invention has improved adsorption capacity and cycle stability. It also effectively avoids the disadvantages of liquid adsorbents that harmful substances are generated during synthesis and use, they are highly corrosive, and they are expensive and harmful to the environment.

[0034] (5) The present invention adopts a solid-phase mixing method and mixes a specific amount of marine biological waste and magnesium oxide, which can give full play to the mutual coordination and synergy between the raw material components and effectively regulate the elemental composition and microstructure of the adsorbent material. With an easy-to-operate and low-cost preparation method, the obtained new carbon dioxide adsorbent can improve the CO2 adsorption capacity and cycle stability of MgO, and can stably maintain a high carbon dioxide adsorption rate and adsorption capacity for a long time.

[0035] (6) The present invention adopts a solid phase reaction method to prepare a magnesium-based adsorbent by directly heating a magnesium source and a bioshell material having a porous structure and a large specific surface area. The obtained powder particles are free of agglomeration and have good filling properties. The operation is simple and the cost is relatively low, which is suitable for large-scale production.

[0036] In summary, the novel low-cost adsorbent preparation method proposed in the present invention uses marine biological waste as the production raw material, which is widely available and cheap; the production process is simple, suitable for large-scale production, and avoids highly toxic solvents. In addition, the solid phase mixing method used in the synthesis method does not require the use of solvents, and it also has the advantages of high selectivity and high yield, simple process, uniform particle size, controllable force, less pollution, avoidance or reduction of hard agglomeration phenomenon that is easy to occur in the liquid phase, and low cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 It is a comparison chart of the adsorption amount of the embodiment of the present invention and the powders doped with different types of marine biological waste in the same proportion.

[0038] Figure 2 MgO-10A (at 380°C during adsorption) of Example 1 of the present invention and oyster shell powder in different proportions

[0039] Figure 3 This is a comparison curve of carbon dioxide adsorption in cyclic experiments with different doping ratios.

[0040] Figure 4 XRD patterns of fresh samples and samples after cycling experiment.

[0041] Figure 5 This is a SEM scanning electron microscope image of a fresh sample.

[0042] Figure 6 This is the SEM scanning electron microscope image of the sample after the cycle experiment.

[0043] Figure 7 This is the energy spectrum image of the fresh sample.

[0044] Figure 8 TEM image and energy spectrum of the sample MgO-10A with the optimal doping ratio.

[0045] Fig. 9 The nitrogen adsorption-desorption curve and pore size distribution curve of MgO-10A, the sample with the best doping ratio.

[0046] Fig.10 is the specific surface area value of samples with different doping ratios. DETAILED DESCRIPTION

[0047] The present invention is further described below in conjunction with specific embodiments, but the present invention is not limited in any way.

[0048] The present invention discloses a method for preparing a carbon dioxide adsorbent, comprising the following steps:

[0049] (1) The bioshell material is washed and then dried to obtain a pretreated bioshell material.

[0050] Specifically, in order to improve the performance of MgO, the present invention adopts marine biological wastes such as oyster shells (mainly composed of aragonite calcium carbonate, accounting for about 95% to 98%), white clam shells (mainly composed of calcite calcium carbonate and aragonite calcium carbonate, accounting for about 90% to 95%), mussel shells (mainly composed of calcite calcium carbonate, accounting for about 95% to 99%), and scallop shells (mainly in two crystal forms, calcite and aragonite, accounting for about 90% to 95%), which are naturally formed and exist in large quantities in nature, and dopes and modify pure MgO to obtain adsorbent material nA-MgO, wherein A is one or a combination of oyster shell, white clam shell, mussel shell, and scallop shell powder, and n is the mass fraction of the doped shell powder.

[0051] In a specific embodiment, the drying temperature is 100° C. to 150° C., and the drying time is 12 h to 24 h.

[0052] (2) Grinding the pretreated biological shell material to obtain shell coarse powder.

[0053] In a specific embodiment, grinding specifically comprises the following steps:

[0054] The pretreated bioshell material is crushed and ground for 1h to 2h, then a 600-mesh to 1200-mesh sieve is used to sift out the powder, the remaining bioshell fragments in the sieve are collected and ground again for 0.5h to 1h, the powder is collected, and the operation is repeated 3 to 6 times.

[0055] (3) The shell coarse powder is calcined under a protective atmosphere, and the calcined product is ground after cooling to room temperature to obtain shell fine powder.

[0056] In a specific embodiment, the calcination comprises: calcining at 200°C to 400°C for 1h to 2h, then heating to 700°C to 900°C at a heating rate of 10°C / min to 20°C / min and calcining for 5h to 10h. Preferably, calcining at 200°C to 400°C for 2h, then heating to 700°C to 900°C at a heating rate of 10°C / min and calcining for 5h.

[0057] (4) The shell micropowder and magnesium oxide solid phase are mixed, the mixed product is calcined under a protective atmosphere, and then ground to obtain a carbon dioxide adsorbent.

[0058] In a specific embodiment, the mass ratio of shell micropowder to magnesium oxide is 1:(1-9).

[0059] Preferably, when the biological shell material is oyster shell, the mass ratio of shell powder to magnesium oxide is 1:9.

[0060] In a specific embodiment, the calcination includes: calcining at 400°C to 5000°C for 1h to 2h, then heating to 500°C to 600°C at a heating rate of 10°C / min to 20°C / min and calcining for 1h to 2h.

[0061] In a specific embodiment, the particle size of the carbon dioxide adsorbent is 40 microns to 125 microns.

[0062] In a specific embodiment, the particle size of the shell powder is 40 microns to 125 microns.

[0063] The present invention also discloses a carbon dioxide adsorbent prepared by the preparation method of any embodiment of the present invention.

[0064] The present invention also discloses the use of a carbon dioxide adsorbent prepared by the preparation method of any embodiment of the present invention in capturing carbon dioxide.

[0065] In a specific embodiment, the carbon dioxide adsorbent is used to adsorb carbon dioxide from air and flue gas.

[0066] In a specific embodiment, the temperature at which the carbon dioxide adsorbent adsorbs carbon dioxide is 300°C to 500°C.

[0067] Specifically, the present invention uses marine biological waste that is naturally formed and exists in large quantities in nature, and dopes and modifies pure MgO to obtain an adsorbent material. Among them, the shell powder made by high-temperature calcination and crushing of biological shell materials is composed of calcium carbonate, and the calcium carbonate is evenly dispersed in the flaky MgO, thereby reducing the occurrence of sintering. At the same time, the marine biological shell has a unique porous structure, which helps to increase the specific surface area and porosity of the adsorbent, and the presence of calcium carbonate can increase the alkalinity of the adsorbent, making it more efficient in adsorbing CO2. In addition, marine biological shells are waste resources with abundant sources and low costs. The use of these wastes is conducive to environmental protection and resource recycling.

[0068] The following are specific embodiments

[0069] Example 1

[0070] The method for preparing the carbon dioxide adsorbent of this embodiment comprises the following steps:

[0071] (1) Oyster shells of the same species and suitable size were selected, rinsed with clean water to ensure that they did not contain other impurities, and dried at 120°C for 2 h to obtain pretreated biological shell materials.

[0072] (2) The pretreated biological shell material was crushed and ground for 2 h, and then 1200-mesh sieve was used to sieve out oyster shell powder in batches and put into sample test tubes for later use.

[0073] (3) Pour the oyster shell powder into a crucible, place it in a muffle furnace under air or nitrogen atmosphere, calcine it at 300 °C for 2 h, then increase the temperature to 850 °C at a heating rate of 10 °C / min and calcine it for 5 h. When the temperature in the furnace drops to room temperature, take it out and grind it, and collect it for later use.

[0074] (4) The mass ratio of oyster shell powder to magnesium oxide was set to 1:9. 1 g of oyster shell powder and 9 g of MgO powder were weighed using an analytical balance. The weighed oyster shell powder and MgO powder were poured into a mortar and fully ground for about 1 h. The ground mixed powder was placed in a crucible and transferred to a muffle furnace set at 550 °C and calcined for 3 h to obtain a carbon dioxide adsorbent.

[0075] Comparative Example 1

[0076] The difference between this comparative example and Example 1 is that magnesium oxide doped with mussel shells is used as the carbon dioxide adsorbent.

[0077] Comparative Example 2

[0078] The difference between this comparative example and Example 1 is that magnesium oxide doped with carapace shells is used as the carbon dioxide adsorbent.

[0079] Comparative Example 3

[0080] The difference between this comparative example and Example 1 is that scallop shell-doped magnesium oxide is used as the carbon dioxide adsorbent.

[0081] Comparative Example 4

[0082] The difference between this comparative example and Example 1 is that undoped magnesium oxide is used as the carbon dioxide adsorbent.

[0083] Comparative Example 5

[0084] The difference between this comparative example and Example 1 is that magnesium oxide doped with 5 mass% oyster shell powder is used as the carbon dioxide adsorbent.

[0085] Comparative Example 6

[0086] The difference between this comparative example and Example 1 is that magnesium oxide doped with 8% by mass of oyster shell powder is used as the carbon dioxide adsorbent.

[0087] Comparative Example 7

[0088] The difference between this comparative example and Example 1 is that magnesium oxide doped with oyster shell powder in a mass fraction of 12% is used as the carbon dioxide adsorbent.

[0089] Comparative Example 8

[0090] The difference between this comparative example and Example 1 is that magnesium oxide doped with 15% by mass of oyster shell powder is used as the carbon dioxide adsorbent.

[0091] Comparative Example 9

[0092] The difference between this comparative example and Example 1 is that magnesium oxide doped with 25% by mass of oyster shell powder is used as the carbon dioxide adsorbent.

[0093] Comparative Example 10

[0094] The difference between this comparative example and Example 1 is that magnesium oxide doped with 35% by mass of oyster shell powder is used as the carbon dioxide adsorbent.

[0095] Comparative Example 11

[0096] The difference between this comparative example and Example 1 is that magnesium oxide doped with oyster shell powder in a mass fraction of 55% is used as the carbon dioxide adsorbent.

[0097] Test Case

[0098] The carbon dioxide adsorbent obtained in Example 1 and Comparative Examples 1, 2 and 3 was placed in an adsorption experimental device for experiment. First, the type and flow rate of the intake air were adjusted, and the flow rate of the nitrogen gas was adjusted to 150 ml / min. Then 0.3 g of the adsorbent was placed in a tubular furnace, and the temperature was raised to 550°C to start calcination. After calcination, the sample was taken out of the tubular furnace, weighed and recorded on an analytical balance. Subsequently, the type and flow rate of the intake air were adjusted, and the flow rate of the carbon dioxide gas was adjusted to 200 ml / min. The sample was placed in the tubular furnace again, and the temperature was raised to 280°C to start carbonation. After the carbonation is completed, the sample is taken out from the tubular furnace, weighed and recorded on an analytical balance. The carbon dioxide adsorption amount of the adsorbent sample is calculated, and the result is as follows: Figure 1 shown.

[0099] Depend on Figure 1 It can be seen that the carbon dioxide adsorbent prepared by the present invention has better adsorption capacity than Comparative Example 1, Comparative Example 2, and Comparative Example 3.

[0100] In order to further study the stability of the solid carbon dioxide adsorbent prepared by the present invention, the present invention conducted a single adsorption test on the carbon dioxide adsorbent prepared in Example 1 and the adsorbents of Comparative Examples 4, 5, 6, 7, 8, 9, 10 and 11. The results are as follows: Figure 2 shown.

[0101] Depend on Figure 3 It can be seen that the carbon dioxide adsorbent prepared by the present invention can still maintain a relatively high carbon dioxide adsorption capacity after undergoing 10 adsorption-desorption cycles.

[0102] From the particle morphology of electron microscope images ( Figure 5 , Figure 6 ), the 10% doped sample (c) shows a relatively tight and regular arrangement compared to other doping ratios (such as 8% and 12%), which helps to form a higher specific surface area, thereby enhancing the adsorption performance of CO2. After 10 cycles of adsorption and desorption tests, it can be seen from the surface morphology that the 10% doped sample still has a relatively loose and porous structure compared to the other three samples. This also explains why the adsorption capacity of MgO-10A is slightly higher than that of other samples. The energy spectrum shows that CaCO3 is evenly distributed in MgO ( Figure 7 ).

[0103] Figure 8 The results show that CaCO3 particles are attached to the flaky MgO as observed by transmission electron microscopy (TEM), indicating that CaCO3 and MgO are physically combined and no new compounds are produced. CaCO3 particles are attached to the MgO flaky structure, increasing the overall specific surface area. This increase in surface area provides more adsorption sites for carbon dioxide molecules, thereby improving the adsorption capacity. In particular, the flaky MgO structure already has a large surface area, and the attached CaCO3 particles further enhance this property. Moreover, the attachment of CaCO3 particles may help to form more microporous structures, and these pore structures can effectively improve the diffusion efficiency of CO2 molecules.

[0104] Fig. 9 The isotherm shown is consistent with the type IV isotherm in the IUPAC classification, with a clear hysteresis loop. This type of isotherm usually appears in materials with a mesoporous structure, indicating that there are a large number of mesopores in the material.

[0105] from Fig. 9It can be seen that there is a significant peak in the pore size range of 2-4nm. According to the IUPAC pore size classification, these pores belong to the mesoporous range (2-50nm), which is consistent with the previous analysis of the nitrogen adsorption-desorption isotherm, indicating that the material is mainly a mesoporous material. The mesopores in this peak area help provide a larger surface area, which is conducive to the adsorption of gases, especially for the capture and storage of carbon dioxide. Although there is no obvious micropore peak in the figure, some small pores below 2nm still exist, indicating that the material may also contain some micropores. The presence of these micropores helps to provide a higher specific surface area, thereby improving the adsorption capacity of the material.

[0106] Specific surface area results ( Fig.10 ) shows that the specific surface area of ​​the adsorbent sample MgO-10A doped with 10% mass fraction is higher than that of the others, which is consistent with the previous SEM electron microscopy image analysis results.

[0107] In summary, the carbon dioxide adsorbent of the present invention has good carbon dioxide adsorption capacity and cyclic regeneration stability, especially the carbon dioxide adsorbent prepared under the conditions of Example 1.

[0108] It can be seen that the preparation method of the present invention is simple, does not require the addition of additional reagents, has stable performance, is environmentally friendly and easy to degrade, and has no additional pollution; moreover, the carbon dioxide adsorbent can significantly improve the stability of the adsorbent regeneration while maintaining a relatively high carbon dioxide adsorption capacity, greatly improves the life and long-term cycle service life of the carbon dioxide solid adsorbent, and can be widely used in the capture process of carbon dioxide gas.

[0109] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a carbon dioxide adsorbent, characterized in that: The following steps are involved: (1) washing the biological shell material and then drying it to obtain a pretreated biological shell material; wherein the biological shell is an oyster shell; (2) grinding the pretreated biological shell material to obtain shell coarse powder; (3) calcining the coarse shell powder under a protective atmosphere, and grinding the calcined product after cooling to room temperature to obtain shell fine powder; (4) The shell micropowder and magnesium oxide solid phase are mixed, the mixed product is calcined under a protective atmosphere, and then ground to obtain the carbon dioxide adsorbent.

2. The preparation method according to claim 1, characterized in that: The biological shell material is oyster shell.

3. The preparation method according to claim 1, characterized in that: In step (1), the drying temperature is 100° C. to 150° C.; and the drying time is 12 h to 24 h.

4. The preparation method according to claim 1, characterized in that: In step (2), the grinding specifically comprises the following steps: The pretreated bioshell material is crushed and ground for 1h to 2h, then a 600-mesh to 1200-mesh sieve is used to sift out the powder, the residual bioshell fragments in the sieve are collected and ground again for 0.5h to 1h, the powder is collected, and the operation is repeated 3 to 6 times.

5. The preparation method according to claim 1, characterized in that: In step (3), the calcination comprises: calcining at 200°C to 400°C for 1h to 2h, then heating to 500°C to 600°C at a heating rate of 10°C / min to 20°C / min and calcining for 1h to 2h.

6. The preparation method according to claim 1, characterized in that: In step (4), the mass ratio of the shell powder to the magnesium oxide is 1:(1-9); The calcination comprises: calcining at 200°C to 4000°C for 1h to 2h, then heating to 500°C to 600°C at a heating rate of 10°C / min to 20°C / min and calcining for 1h to 2h.

7. The preparation method according to claim 1, characterized in that: The particle size of the shell micropowder is 40 microns to 125 microns; The particle size of the carbon dioxide adsorbent is 40 microns to 125 microns.

8. A carbon dioxide adsorbent prepared by the preparation method according to any one of claims 1 to 7.

9. Use of a carbon dioxide adsorbent prepared by the preparation method according to any one of claims 1 to 7 in capturing carbon dioxide.

10. The use according to claim 9, characterized in that: The carbon dioxide adsorbent is used for adsorbing carbon dioxide in air and flue gas.

Citation Information

Patent Citations

  • A material compound and a method of fabricating the same

    CN101378992A

  • Method for preparing mussel shell powder / carboxymethyl cellulose composite gel adsorbent

    CN110721664A

  • Carbon dioxide capture from a cement manufacturing process

    US20100319586A1

Cited By

  • CO2 adsorbent and preparation method thereof

    CN120054445A

  • Method for preparing Ca-based CO2 adsorbent based on co-treatment and synergism of organic shellfish shell waste

    CN122183563A

  • Method for preparing derivative nano calcium-based CO2 adsorbent by utilizing shellfish shell waste

    CN122343039A

  • A method for preparing a derived nano calcium-based co2 adsorbent using shell waste of shellfish

    CN122343039B